Uji Kepribadian Sebagai Penunjang Keputusan Penerimaan, Penyaringan, serta Penugasan Karyawan pada Universitas Menggunakan Prosedur MBTI - Rizky Eka Febriansah; Vera Firdaus (Politeknik Negeri Batam, 2022)
The purpose of the research is to increase the effectiveness of HR management activities at the university, especially in the aspect of employee recruitment, employee selection, and employee assignment so that new employees who are accepted into or old employees who are placed in new positions can provide maximum performance impact for the organization. The research method used is descriptive qualitative research. The sample used is all structural employees who work at the University of Muhammadiyah Sidoarjo campus 1 which contains 57 people. The results of research recommendations for the University of Muhammadiyah Sidoarjo are stated in the table provided in the results and discussion section which contains conclusions and suggestions for the suitability between the job description of a position and the appropriate Myers Briggs Type Indicator personality mechanism.